A Road Map: E- Commerce to World Wide Web Growth of Business World (Global Journal of Management and Business Research, 2019)
In this research article the researcher emphasized that significant role of E-commerce to world wide web growth of business world with respect to technology of internet, sharing business information, conducting business transaction, the emergence of the new system, better business policy, creating value of customers, proper utilization of resources and organizational infrastructure making a drastic and radical changes in business world. The incredible growth in mobile phone access shows that majority of people have adapted to mobile phone and advancement in mobile technology and its usage is not limited for making basic phone calls, but can be used almost in every sector of human activity if one has the required technological knowledge. Since the time e-commerce has evolved, the world of business has observed a drastic change in the way trade activities are conducted. With the increase in the growing competition and its complexity it is essential for today's business enterprises to work in structured manner by changing its functioning environment dynamically by integrating internal information resources to the platform of ERP systems which will assist in optimizing potential of utilizing resources efficiently and determining growth.
Keywords: e-commerce; ERP; B2B; SME